PRODUKTIVITAS SAWIT DAN EVALUASINYA (PALM PRODUCTION AND EVALUATION) - Sitohang, Nurdin (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The average potency of palm production were 24, 22, 20, and 18 ton fruit fresh bunch (FFB) each year along 25 years in class of land 1, 2, 3 and 4. In fact, the real production of palm is often below of planning (estimation). Production evaluation ought to be done as dayly, weekly, monthly, threemonthly, sixmonthly, and yearly. Several points of production evaluation of palm as like: comparing with last year production, tendency of production, palm condition in field, maintainance of palm, harvest system, and solving some problems in field. The object of production evaluation would be done with overall of plantation, every afdeling, groups of years planting (groups of age plantings), and every blocks land area. The result of evaluation would be used as based information to repair/maintain palm, to increase the product and to stabilize the high product, or in other term to optimize the production as good as land potency.